(151) تقدير مصفوفة حسابات إجتماعية للاقتصاد المصري عام (1998-1999) Estimation of a Social Accounts Matrix for the Egyptian Economy in 1998-1999. - سهير أبو العينين (معهد التخطيط القومي،, 2018)
إبريل 2002.